Scheduling Flexible Manufacturing System with Stacker Crane Using Coloured Petri Nets - Ari Setiawan; Teguh Ersada Natail Sitepu (Jurnal Teknik Industri, 2018)
Scheduling Flexible Manufacturing System (FMS) can increase production speed and accuracy. It because FMS has an ability to process various variety of product at same work station. However, FMS need efficient allocation of resources, for example: allocation of material handling equipment. This paper presents production scheduling FMS modelling to 24 jobs and 4 machines considering stacker crane. Coloured Petri Nets (CP-Nets) is the programming language which used to simulate model because it’s simplicity. This model consists two main model activities. The first one is Physical Activity (PA) which related to every activity that involve physical movement, including stacker crane processes. PA consist five CP-Nets models: loading/unloading station, stacker crane, machine, picking mechanism, and pallet stocker. The second activity is Logical Expression (LE) which related to the rules on how FMS should operate. LE consist three CP-Nets models: machine selection, pick-up request, and stage two procedure.  A simulation and numerical report show utilization level of all machines around 80-84% and stacker crane 8,74%.